Jaw locking after maxillofacial trauma - David B. Kamadjaja; R. Soesanto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
The purpose of this report is to present two cases of jaw locking with two different etiologies. In case #1, jaw locking occured 5.5 months after a surgical reduction and internal fixation on the fractured maxilla and mandible. Some plain radiographic x-ray were made but failed to give adequate information in establishing the cause of trismus. The three dimensional computed tomography (3D-CT) was finally made and able to help guide the pre-operative diagnosis and treatment. Two-steps gap arthroplasty were done comprising a gap arthroplasty leading to acceptable outcome. An adult patient in case #2 with a history of trauma at his childhood and bird-like face apprearance clinically, was unable to open the mouth since the time of accident. The patient was diagnosed with bilateral ankylosis of temporomandibular joints. One side (right) gap arthroplasty was done and resulted in normal mouth opening.